Modelling Rarefied Hypersonic Reactive Flows Using the Direct Simulation Monte Carlo Method (Communications in Computational Physics, 2020)
This paper presents the implementation, validation and application of TCE(total collision energy) model for simulating hypersonic reactive flows in a paralleldirect simulation Monte Carlo code, named PDSC++, using an unstructured grid. Aseries of benchmarking test cases, which include reproduction of theoretical rate constantsin a single cell, 2D hypersonic flow past a cylinder and 2D-axisymmetric hypersonicflow past a sphere, were performed to validate the implementation. Finally,detailed aerothermodynamics of the flown reentry Apollo 6 Command Module at 105km is simulated to demonstrate the powerful capability of the PDSC++ in treatingrealistic hypersonic reactive flow at high altitude.